2018
DOI: 10.1159/000484111
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Submucosal Dissection for Adenocarcinomas of the Esophagogastric Junction

Abstract: Background: Adenocarcinoma of the esophagogastric junction (EGJ) is uncommon in Eastern countries, including Japan, but it is believed that the incidence of EGJ adenocarcinoma will increase in Asia in the future due to the decreasing incidence of Helicobacter pylori infection. Endoscopic submucosal dissection (ESD) is a minimally invasive and curative treatment that allows precise pathological assessment. Summary: Magnifying endoscopy with narrow-band imaging may be useful for differential diagnoses and for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…Endoscopic submucosal dissection (ESD) emerged as an endoscopic treatment for gastrointestinal tumors in the 1990s and is now widely used as a beneficial curative therapy owing to its minimal invasiveness and good postoperative outcomes in activities of daily living. The use of ESD for superficial esophageal carcinoma is particularly advantageous in terms of postoperative activities of daily living compared with surgery [1][2][3]; however, a number of procedural accidents, including perforations, can occur during ESD [4][5][6]. The esophagus is anatomically characterized by the absence of a serosa, which means that mediastinal emphysema can occur with ESD, even without perforation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic submucosal dissection (ESD) emerged as an endoscopic treatment for gastrointestinal tumors in the 1990s and is now widely used as a beneficial curative therapy owing to its minimal invasiveness and good postoperative outcomes in activities of daily living. The use of ESD for superficial esophageal carcinoma is particularly advantageous in terms of postoperative activities of daily living compared with surgery [1][2][3]; however, a number of procedural accidents, including perforations, can occur during ESD [4][5][6]. The esophagus is anatomically characterized by the absence of a serosa, which means that mediastinal emphysema can occur with ESD, even without perforation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…ESD has been accepted as the minimally invasive curative treatment option for superficial early gastrointestinal cancers including those of stomach, esophagus and colonic origins [24] . However, the indication of endoscopic treatment for early GEJ cancers including Barret's adenocarcinoma has not been clearly established due to unclear pattern of lymph node metastasis [25] . Meta-analysis of 6 retrospective studies have demonstrated the safety and feasibility of ESD on early superficial GEJ cancers [26] .…”
Section: Role Of Endoscopic Treatment In Early Stage Gej Cancermentioning
confidence: 99%
“…Even in Asia, including Japan, there is concern that the incidence of esophagogastric junctional adenocarcinoma will increase following a decrease in the H. pylori infection rate [2,3]. Early stage adenocarcinoma of the EGJ can be endoscopically resected, such as by endoscopic submucosal dissection (ESD), and is expected to achieve good oncological outcomes [4][5][6]. On the other hand, the prognosis of advanced esophageal adenocarcinoma, including esophagogastric adenocarcinoma and Barrett's adenocarcinoma, is poor, and its early detection is necessary for better prognosis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%